STIMULASI HASIL MELON ( Cucumis melo, L) DENGAN MENGGUNAKAN BIOTO GROW GOLD (BGG) - SAHINDAH ARITONANG; SURTINAH SURTINAH (Jurnal Ilmiah Pertanian, 2018)
The experiment was conducted experimentally using non-factorial Randomized Design (RAL) with 5 (five) treatment levels without Bioto Grow Gold, Bioto Grow Gold 1 ml liter-1 water, Bioto Grow Gold 2 ml liter -1 water, giving Bioto Grow Gold 3 ml liter-1 water and giving Bioto Grow Gold 4 ml liter-1 water. The data analysis used variance and continued with a different test of Duncan treatment average at p 0.05. The results showed that BGG treatment had the significant effect on leaf length, leaf width, stem diameter, flowering age, fruit circumference, fruit weight, a thickness of flesh and sugar content of melon fruit. The best treatment is giving Bioto Grow Gold 3 ml liter-1 water.